2022
DOI: 10.3389/fimmu.2022.883116
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-1: A Promising Target for the Treatment of Allergic Diseases

Abstract: Thioredoxin-1 (Trx1) is an important regulator of cellular redox homeostasis that comprises a redox-active dithiol. Trx1 is induced in response to various stress conditions, such as oxidative damage, infection or inflammation, metabolic dysfunction, irradiation, and chemical exposure. It has shown excellent anti-inflammatory and immunomodulatory effects in the treatment of various human inflammatory disorders in animal models. This review focused on the protective roles and mechanisms of Trx1 in allergic disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 114 publications
(137 reference statements)
0
9
0
Order By: Relevance
“…The C32S/C35A mutation is prevalent in various diseases, including diabetes, cardiovascular and cerebrovascular disorders, as well as immune system dysfunctions [ 210 , 243 , 250 , 251 ]. This C32S/C35A mutation leads to a reduction in the expression of genes involved in insulin secretion, glucose uptake, metabolic regulation, immune activation, differentiation, and regulation [ 252 , 253 ].…”
Section: The Interplay Between Trx and Cellular Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…The C32S/C35A mutation is prevalent in various diseases, including diabetes, cardiovascular and cerebrovascular disorders, as well as immune system dysfunctions [ 210 , 243 , 250 , 251 ]. This C32S/C35A mutation leads to a reduction in the expression of genes involved in insulin secretion, glucose uptake, metabolic regulation, immune activation, differentiation, and regulation [ 252 , 253 ].…”
Section: The Interplay Between Trx and Cellular Senescencementioning
confidence: 99%
“…Besides the four most common and concerned age-related diseases mentioned above, Trx-mediated redox regulation plays a crucial role in the occurrence and development of immune system disorders and musculoskeletal diseases. These diseases are usually characterized by inflammation and oxidative stress, and their pathogenic mechanisms are extensively linked to Trx, such as chronic kidney disease (CKD), rheumatoid arthritis (RA), allergic diseases, osteoporosis, osteoarthritis, and other diseases [ [336] , [337] , [338] , [339] ]. These diseases are especially relevant in the context of aging, and have a significant impact on the elderly.…”
Section: Relationship Between Trx-mediated Alterations In Redox Statu...mentioning
confidence: 99%
“…The findings of the study suggested that quercetin may have a therapeutic effect on AR by influencing the behaviour of HNEpC cells [ 62 ]. Thioredoxin (TRX) is a protein known for regulating oxidative metabolism and neutralizing reactive oxygen species, which play a role in suppressing allergic inflammation [ 63 ]. A study determined quercetin’s impact on AR symptoms and TRX production in nasal cells both in vitro and in vivo.…”
Section: Nutraceuticals and Allergic Rhinitis (Ar)mentioning
confidence: 99%
“…Thioredoxin-1 (Trx-1), a multifunctional redox protein, can directly eliminate ROS and maintain the redox balance in mammalian cells ( Zeng et al, 2018 ). Various stress conditions could upregulate the expression of Trx-1 ( Jia et al, 2014 , 2016 ; Wang et al, 2022b ; Zeng et al, 2020 ). Accumulating researches have demonstrated that Trx-1 has neuroprotective effects in common neurodegenerative diseases, including AD ( Jia et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%